Simulation of Cofferdam Calculations Using Geo-Studio Application in Peusangan Hydropower Dam Construction - Hermansyah, Hermansyah; Irwan, Irwan; Satria, Habib; Dayana, Indri; Salam, Rudi (Andalasian International Journal of Applied Science, Engineering and Technology, 2023)
Cofferdam is a building in the form of earth, stone, concrete or masonry filling and holds water, prevents flooding, provides irrigation. The building has many functions such as for agriculture, power generation, and tourist attractions. Cofferdam will also be very helpful in flood control which will control flood water so that it will not overflow excessively which endangers the surrounding community. Besides having great benefits. If the cofferdam collapses (broken) it will cause flash floods that result in casualties. Therefore the cofferdam must be designed safely and technically feasible. The research approach used in this study is a quantitative approach using the 2012 GEO-SLOPE program. The conclusions from the analysis of slope seepage and seepage stability are the Critical Safety Factors for cofferdam stability according to the results of the analysis after running SLOPE/W are 1.711 & 1.512 because it is higher than 1.5 (SNI 8460:2017 Geotechnical Requirements Design, This means that the stability of the cofferdam is safe. The modeling results show that the seepage discharge is 1.81x10-7 m3/s = 1.81x10-4 liters/sec = 15.64 liters/day which is smaller than the maximum allowable discharge of 50 liters/day. So it can be concluded that the seepage discharge is safe.